Humanity in crisis : ethical and religious response to refugees - Hollenbach, David, 1942- (Moral traditions series., 2019)
The major humanitarian crises of recent years are well known: the Shoah, the killing fields of Cambodia, Rwandan genocide, the massacre in Bosnia, the tsunami in southeast Asia, not to mention bloody conflicts in Sudan, Syria, and Afghanistan. Millions have been killed and many millions more have been driven from their homes; the world is sadly full of refugees and internally displaced persons. Could these crises have been prevented? Why do they continue? This book seeks to understand how humanity is in crisis, and what we can do about it. Hollenbach draws on the values that have shaped major humanitarian initiative over the past century and a half, such as the commitments of the International Committee of the Red Cross, Oxfam, Doctors without Borders, as well as the values of religious and ethical traditions, to examine the scope of our responsibilities and practical solutions to these global crises. He also explores the economic and political causes of these tragedies, drawing on on-the-ground interviews with refugees and government and NGO leaders, and uncovers key moral issues for practitioners in the field.